Porphyromonas gingivalis-Derived Lipopolysaccharide Combines Hypoxia to Induce Caspase-1 Activation in Periodontitis - Cheng, Ran; Liu, Wen; Zhang, Rui; Feng, Yuchao; Bhowmick, Neil A.; Hu, Tao (Frontiers in Cellular and Infection Microbiology, 2017)
Periodontitis is defined as inflammation affecting the supporting tissue of teeth. Periodontal pathogens initiate the disease and induce inflammatory host response. Hypoxia may accelerate the process by producing pro-inflammatory factors. The aim of this study is to investigate the effect of Porphyromonas gingivalis (P. gingivalis) lipopolysaccharides (LPS) and Escherichia coli (E.coli) LPS in inducing caspase-1 activation in normoxic or hypoxic phases. The results showed that healthy gingiva was in a normoxic phase (HIF-1α negative). However, hypoxia appeared in periodontitis, in which NLRP3, cleaved-caspase-1, interleukin 1 beta (IL-1β) and caspase-1-induced cell death was enhanced in periodontitis specimens. The in vitro experiment showed that P. gingivalis LPS slightly decreased the level of NLRP3 and IL-1β in gingival fibroblasts under normoxia. Surprisingly, hypoxia reversed the effects of P. gingivalis LPS, highly promoted caspase-1 activation and IL-1β maturation. E.coli LPS, a kind of pathogen-associated molecular pattern (PAMP) was chosen to simulate the effect of Gram-negative microbiota. Different from P. gingivalis LPS, E.coli LPS enhanced IL-1β maturation both in normoxia and hypoxia. Moreover, E.coli LPS turned normoxia into hypoxia phase in experimental periodontitis model, which may subsequently propel the inflammatory effect of P. gingivalis LPS. It was concluded that E.coli LPS induced a hypoxic phase, which is a combing pathological factor of P. gingivalis LPS in caspase-1 activating and IL-1β maturation in periodontal inflammation.